Levels of Cognition in Reading Text National Examination Year 2005-2011 Based on Bloom’s Taxonomy - Bertaria Sohnata Hutauruk (Universitas Bunda Mulia, 2017)
This study was conducted to identify and analyze the level of cognition in reading section of national examination 2005-2011 for Vocational School. The problems of this study were formed as follows: (1) How is the percentage of the level of cognition in reading section of national examination 2005-2011 for Vocational School? (2) What level of cognition is dominantly examined for reading section of national examination 2005-2011 for Vocational School? To solve the problems, the writer used Bloom’s taxonomy (1956), Krathwohl (2002), Sternberg & Williams (2009), Henning (2001), and Gronlund (1985). This study was a qualitative research which was conducted by applying documentation analysis. The subjects of this research were the documents of national examination questions for Vocational School (SMK) from year 2005 to 2011. The object of this research was the level of difficulties of reading section questions. The writer finds out that the levels of cognition, which are examined for reading section of national examination from year 2005-2011, are comprehension for 55,8%, analysis for 25%, and knowledge for 19,2 %. Other levels such as: application, synthesis, and evaluation are null. This also means that comprehension is the most dominant level of cognition that has been examined in National Examination. In conclusion, this study shows that application is more suitable for performance test. Synthesis and evaluation are more appropriate if they are tested in form of essay because those kinds of question need to be elaborated with some examples and opinion. The researcher suggests the English teachers, especially those who teach the last year students to guide and motivate the students to prepare themselves before taking examination. Keywords: cognition, examination, reading text